2003
DOI: 10.2306/scienceasia1513-1874.2003.29.109
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: To investigate the antioxidant defense system, salt-stress induced changes of antioxidant enzymes were examined in the leaves of mulberry (Morus sp.) of the salt-tolerance cultivar Pei. With increasing salinity up to 150 mM NaCl, the hydrogen peroxide content and the activity of guaiacol-specific peroxidase increased markedly. In addition, the activities of superoxide dismutase, ascorbate peroxidase and glutathione reductase slightly increased at 150 mM NaCl. In contrast, catalase activity with increasing sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(20 citation statements)
references
References 14 publications
2
15
0
1
Order By: Relevance
“…The responses of antioxidant enzymes to UV radiation vary among plants species ) Tossi et al, 2009;Salama et al, 2011;Czégény et al, 2016(. The increasing in the activities of antioxidant enzymes could be the indicator of build-up of a protective mechanism to reduce oxidative damages induced by stress (Harinasut et al, 2003;Chawla et al, 2013). According to results obtained from this study, the produced H 2 O 2 effectively removed by POD and especially CAT in plants fed with concentration of 6.5 µm Zn.…”
Section: Antioxidant Systemsupporting
confidence: 54%
See 1 more Smart Citation
“…The responses of antioxidant enzymes to UV radiation vary among plants species ) Tossi et al, 2009;Salama et al, 2011;Czégény et al, 2016(. The increasing in the activities of antioxidant enzymes could be the indicator of build-up of a protective mechanism to reduce oxidative damages induced by stress (Harinasut et al, 2003;Chawla et al, 2013). According to results obtained from this study, the produced H 2 O 2 effectively removed by POD and especially CAT in plants fed with concentration of 6.5 µm Zn.…”
Section: Antioxidant Systemsupporting
confidence: 54%
“…The hydrogen peroxide (H 2 O 2 ) content was estimated according to the Harinasut et al (2003). Samples were homogenized with 0.1 % (w/v) trichloroaceticacid (TCA).…”
Section: Hydrogen Peroxide and Malondialdehyde Assaysmentioning
confidence: 99%
“…These results suggest that this antioxidant enzyme has possible defensive role in the removal of H 2 O 2 under salinity stress. The increased total peroxidase activity in response to salinity has been reported (Chen et al 1993;Sreenivasulu et al 2000;Harinasut et al 2003). The plants treated with NaCl in combination with GA 3 and AsA exhibited much higher values for antioxidant enzyme activity than when NaCl was given alone.…”
Section: Discussionmentioning
confidence: 66%
“…It has been reported that ROS, including superoxide and hydrogen peroxide, are elevated with increasing the salinity, due to the imbalance in the production and destruction of ROS (Harinasut et al 2003). In the present study, the P. vulgaris seedlings responded to NaCl treatment with enhancement of H 2 O 2 content, which was higher in the roots than the shoots.…”
Section: Discussionmentioning
confidence: 99%
“…Mulberry is a tree species that is moderately resistant to salt stress [27]. In this study, we found that NaCl-induced salinity stress caused a marked inhibition in the growth of mulberry seedlings as evidenced by changes in the DW of new leaves, shoots, and roots; the lengths of roots and shoots; and the successive increments in leaf number.…”
Section: Discussionmentioning
confidence: 66%